2014
DOI: 10.1002/14651858.cd007479.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pericyazine for schizophrenia

Abstract: On the basis of very low quality evidence we are unable to determine the effects of pericyazine in comparison with typical or atypical antipsychotics for the treatment of schizophrenia. However, there is some evidence that pericyazine may be associated with a higher incidence of extrapyramidal side effects than other antipsychotics, and again this was judged to be very low quality evidence. Large, robust studies are still needed before any firm conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…There is no mention of pericyazine in any guideline on the National Institute for Health and Care Excellence (NICE) website, the main source of clinical guidelines in England. A 2014 Cochrane review on pericyazine identified only 5 studies suitable for inclusion, could not determine the effect of pericyazine in schizophrenia given the low quality of evidence, and found a higher incidence of side effects compared to atypical antipsychotics [ 16 ]. A PubMed search identified only 73 publications that contain the word “pericyazine” [ 17 ] in any way since 1965 compared with over 22,000 results for haloperidol and 11,000 for risperidone.…”
Section: Discussionmentioning
confidence: 99%
“…There is no mention of pericyazine in any guideline on the National Institute for Health and Care Excellence (NICE) website, the main source of clinical guidelines in England. A 2014 Cochrane review on pericyazine identified only 5 studies suitable for inclusion, could not determine the effect of pericyazine in schizophrenia given the low quality of evidence, and found a higher incidence of side effects compared to atypical antipsychotics [ 16 ]. A PubMed search identified only 73 publications that contain the word “pericyazine” [ 17 ] in any way since 1965 compared with over 22,000 results for haloperidol and 11,000 for risperidone.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is no mention of pericyazine in any guideline on the National Institute for Health and Care Excellence (NICE) website 6 , the main source of clinical guidelines in England. A 2014 Cochrane review on pericyazine identified only five studies suitable for inclusion, could not determine pericyazine’s effect in schizophrenia given the low quality of evidence, and found a higher incidence of side effects compared to other antipsychotics 7 . A PubMed search identified only 73 publications that contain the word pericyazine in any way since 1965 compared with over 22,000 results for haloperidol, and 11,000 for risperidone.…”
Section: Discussionmentioning
confidence: 99%
“…76 Parkinson por mais de trinta anos e já descrito por sua ação anticolinesterásica. 83,84,85 Dentre os resultados obtidos, os autores destacam a importância da descoberta da alta potência e seletividade do derivado quinolizidinila (28c), a periciazina, 86 um fármaco antipsicótico com ação sedativa e cujas ações anti-BuChE descobertas merecem melhor investigação para possível emprego no tratamento pacientes com DA associada a desordens psicóticas.…”
Section: Derivados Benzimidazólicosunclassified